Tinjauan Yuridis terhadap Tindak Pidana Persetubuhan dengan Kekerasan pada Anak - Tongat, Tongat; Nugrono, Bastianto; Wibowo, Supolo Satyo (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
The Republic of Indonesia, which is based on Pancasila and the 1945 Constitution, always regulates the behavior of its citizens through a series of regulations that are sourced from law. Cases of child sexual intercourse in this country tend to increase. This is one indicator of the poor quality of child protection. Article 20 of Law Number 35 of 2014 amendments to Law Number 23 of 2002 concerning Child Protection states that: "The State, Government, Regional Government, Community, Family, and Parents or Guardians are obliged and responsible for the implementation of Child Protection." Children who are victims of sexual intercourse will suffer material and immaterial losses that can affect their future lives. There needs to be an optimal effort to improve this condition in accordance with Article 2 Paragraph (3) and (4) of the Law of the Republic of Indonesia Number 4 of 1979 concerning Child Welfare, which states that: "Children have the right to care and protection both during pregnancy and after birth". Children have the right to life protections that can harm or hinder normal growth and development. This research is a normative juridical research that describes in detail social phenomena that are the main problems in everyday life associated with applicable positive criminal law regulations. - other symptoms. This study focuses on secondary data sources obtained from primary legal materials, secondary legal materials and tertiary legal materials. Primary legal materials are in the form of laws and regulations outside the Criminal Code relating to criminal law policy issues against crimes committed against children, such as the Law of the Republic of Indonesia Number 23 of 2002 concerning Child Protection, Law Number 11 of 2012 concerning the Juvenile Justice System which renewed by Law no. 35 of 2014